Analisis Efisiensi Biaya Distribusi Pupuk Bersubsidi di Wilayah Kabupaten Klungkung Menggunakan Metode Transportasi - Febriani, Erni; Widia, I Wayan; Arda, Gede (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 2 (2016): September, 2016)
The aim of this research was to determine the distribution pattern of subsidized fertilizer in Klungkung regency, as well as to determine the distribution pattern of subsidized fertilizer that produced the minimum distribution cost. The research method used in the study, were a survey, measuring the distance and collect secondary data. The survey was conducted to official distributors to obtain the amount of farmer groups which recieved the subsidized fertilizer. The information of farmer groups’ distance to the official distributors, received fertilizer, and the cost spent to distribute the fertilizer were needed to calculate the unit cost of distribution. All of those information were obtained by field survey and direct measurement in location. The data obtained then was analyzed by applying three methods of transportation that was North West Corner Method, the Lowest Cost Method and The Vogel's Approximation Method. The results indicated that the methods produced different costs in which the minimum distribution cost by Rp 6.065.846,00 was produces by the Lowest Cost Method. The value of the result is vsame with the transportation minimum cost that produced by the distribution pattern of subsidized fertilizer at this time in Klungkung regency, so it can be concluded that the distribution pattern of subsidized fertilizer in Klungkung regency at this time is meeting with the all criteria distribution pattern with transportation minimum cost.
Keywords: subsidized fertilizer, farmer group, retailer, distribution cost